INNOVATIONS OF THE DIGITAL ERA AND ECONOMIC CHOICE - Babukh, Ilona; Pochenchuk, Galyna; Baraniuk, Diana (Ștefan cel Mare" Univeristy of Suceava Publishing House, Romania, 2018)
The article deals with the peculiarities of the economic choice from the standpoint of rational choice theory and behavioral economy influenced modern innovative changes. Behavioral economics in recent years has shown significant influence of irrational factors on the behavior of economic actors, acknowledging that the benefits of people are endogenous. In this regard, a fast-growing digital economy does not simply lead to accelerated innovation and its widespread use in many sectors of the economy, but essentially reflects the objective process of the ever-increasing influence of irrational motives in choosing and making decisions by the economic actors. The new digital technologies have expanded the possibility of knowing the motives and reasons that motivate economic agent to make certain choices and adopt new business models. Changing technologies to collect and analyze information, reducing it to a knowledge base. Digital technologies on the basis of the created psychographic profile give an opportunity to influence all components, guiding the economic choice of the individual. Impact tools include, first of all, microtargeting and nudge-tech. Consequently, the possibilities of modern innovative technologies allow us to obtain new behavioral knowledge that helps to clearly formulate value propositions for a particular audience, methods and relevant channels of communication with it, facilitate the successful launch of new products and services, and increase their sales. However, along with the possibilities, digital disruptive innovations also create threats, including manipulations, misuse of personal data, cyber attacks.
Keywords: digital economy; disruptive innovation; economic choice; microtargeting; nudge technology; customer centricity